-8-n=-3(-2n-4)

Simple and best practice solution for -8-n=-3(-2n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-n=-3(-2n-4) equation:


-8-n=-3(-2n-4)

We simplify the equation to the form, which is simple to understand
-8-n=-3(-2n-4)

Reorder the terms in parentheses
-8-n=+(+6n+12)

Remove unnecessary parentheses
-8-n=+6n+12

We move all terms containing n to the left and all other terms to the right.
-1n-6n=+12+8

We simplify left and right side of the equation.
-7n=+20

We divide both sides of the equation by -7 to get n.
n=-2.85714285714

See similar equations:

| 8+3x=20-5x | | -11x-67=-7x+53 | | -8x+16=-20 | | 1x*8+12=-21 | | (W-3)5+7=2 | | 421=-5x+8(8+7x) | | 3(4-2d)-6=2(5d-5) | | 2x+x+10=34 | | -2x-12=3x+3 | | y^2=8y-15 | | x/x+2=4 | | 4x-9=2(2x+7) | | 11+3x=12+5x | | 0=3t-2t | | y=4tanx | | -9x-43=15-11x | | 6x-8x+2=-10 | | p-8.125=16.21 | | (-12)(-13)= | | 5r+10=3r+5-3r | | p-8.125p=16.21 | | 3x*13x+14*4=7 | | 6x-8y-9x-6y= | | x^4+18x^2+69= | | 8v-3v=25 | | -5x-7=11 | | 11x-3=10(x-5)-8 | | 4=5x-3 | | 6x^2-11x+5=3x+17 | | -x-42=4x+33 | | 126-36n=7+2n | | 6v-4=8(v-2) |

Equations solver categories